Bahasa Figuratif dan Citraan Dalam Kumpulan Puisi Hujan Bulan Juni Karya Sapardi Djoko Damono dan Implementasinya Sebagai Bahan Ajar Bahasa Indonesia DI SMA - Arfiana Putri, Novita (2016)
Purpose of this study there were four. (1) Describe the form of background sosiohistoris sapardi djoko damono. (2) describe the use of figurative language in the form of a collection of poetry Rain in June sapardi djoko damono work. (3) describe the use of imagery in the form of poetry Rain in June and works sapardi djoko damono. (4) Describe the implementation of figurative language and imagery in a collection of poetry Rain in June sapardi djoko damono work as teaching materials Indonesian high school. This type of research is qualitative descriptive. The data in this thesis in the form of words, phrases, and sentences in kulmpulan poetry Rain in June sapardi djoko damono work. Sources of data in this thesis is twofold. First, the source of primary data in the form of twelve poems rains in June published by Gramedia Pustaka Utama, the year 2013 which is the third printing with 120 pages thick. Second, secondary data sources include the journals, theses, papers, and articles. Data collected by the engineering literature, see, and record. Data were analyzed using the method of reading semiotic models, ie heuristic and hermeneutic reading. The results of this study: (1) Background sosiohistoris sapardi djoko damono. Sapardi is one of the writers in Indonesia. He was born in Solo, 20 March 1940. (2) In the figurative language of poetry Rain in June Sapardi works only figure of speech and idiomatic speech. There are only five figure of speech in this poem. (a) Figure of speech metaphor. (b) Figure of speech simile. (c) The personification figure of speech. (d) metonemia figure of speech. (e) Sinedoki figure of speech. (3) The images in the collection of poetry Rain in June Sapardi work. (a) Visual imagery (Visual Imagery). (b) Auditory imagery (Auditory Imagery). (c) Motion images (Movement Imagery). (d) The imagery palpability (Tactile / Thermal Imagery). (e) The imagery of smell (Smell Imagery). (f) Intellectual imagery (Intellectual Imagery). (4) Implementation of figure of speech and images in the collection of poetry Rain in June sapardi djoko damono work as teaching materials Indonesian high school that is contained in the standard of competence 14. express opinions to poetry through discussion and basic competence 14.1 discuss the contents with respect to the image sensing poetry, feelings , mind and imagination through discussion and 14.2 connect the poem with the reality of natural, social, cultural, and community through discussion.